2015
DOI: 10.1111/jch.12733
|View full text |Cite
|
Sign up to set email alerts
|

Age‐ and Sex‐Related Differences in Efficacy With an Angiotensin II Receptor Blocker and a Calcium Channel Blocker in Asian Hypertensive Patients

Abstract: Overseas guidelines to manage hypertension recommend selecting different drugs depending on age, but no studies have investigated the relationship between drug selection and age-and sex-related differences, although such information may help to reduce the risk of cardiovascular mortality. The Azilsartan Circadian and Sleep Pressure--the First Study (ACS1) trial was a multicentered, randomized, open-label, two-parallel group study comparing the effects of an angiotensin II receptor blocker (azilsartan) and a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Therefore, identifying factors that would attenuate the adverse renal effect is of great value for therapeutic treatment of hypertension. Other than age, sex, race, and the presence of CKD, which were associated with the risk of acute renal failure when using ARB, 22,42 our study found that vitamin D status, is also a modifiable factor that can be easily targeted in the clinical practice. In addition, vitamin D is a well‐tolerated pleiotropic hormone.…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, identifying factors that would attenuate the adverse renal effect is of great value for therapeutic treatment of hypertension. Other than age, sex, race, and the presence of CKD, which were associated with the risk of acute renal failure when using ARB, 22,42 our study found that vitamin D status, is also a modifiable factor that can be easily targeted in the clinical practice. In addition, vitamin D is a well‐tolerated pleiotropic hormone.…”
Section: Discussionmentioning
confidence: 64%